Phytotoxicity and anti-phytopathogenic activities of marine-derived fungi and their secondary metabolites. Issue 66 (8th November 2018) - Huang, Rui-Huan; Gou, Jian-Yu; Zhao, Dong-Lin; Wang, Dan; Liu, Jing; Ma, Guo-Yong; Li, Yi-Qiang; Zhang, Cheng-Sheng
Abstract : Marine-derived fungi and their secondary metabolites with agricultural bioactivity including phytotoxicity and anti-phytopathogenic activities. Abstract : To find new pesticides for agricultural use, 133 fungal strains were isolated from coastal marine habitats, from which 37 independent isolates were identified, belonging to 20 genera in nine orders, and the diversity of the isolated fungi were discussed. The phytotoxicity and anti-phytopathogenic fungal and bacterial activities of these 37 extracts, and two previously isolated fungal extracts were evaluated, displaying different levels of bioactivity. Based on the bioactive and chemical screening, an Alternaria sp. (P8) strain, which showed prominent bioactivity and contained abundant secondary metabolites was selected for further chemical investigation; one new compound, a benzopyranone (1 ), and seven known compounds (2–8 ) were obtained. Their structures were determined by analysing extensive NMR spectroscopic data and ECD comparisons. Compounds1, 2, and6–8 showed obvious phytotoxicity, especially against amaranth, and compound1 also showed potent antifungal activity toward Alternaria brassicicola . To the best of our knowledge, this is the first report of the phytotoxicity of marine-derived fungi and their secondary metabolites. These studies should provide the foundation for future research into the use of such fungal extracts to combat weeds and diseases in agriculture.